A proteomic and neurochemical analysis of the effects of early life stress on drug addiction and post abuse therapeutic interventions : an animal study - Faure, Jacqueline Jeanette (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Biomedical Sciences. Medical Physiology))--University of Stellenbosch, 2010.